Womens Empowerment Management Models For Local Economic Development - I Gusti Ayu Purnamawati; Gede Adi Yuniarta (Relevance: Journal of Management and Business, 2020)
The efforts to realize gender equality through the work of Balinese women were built from the endek weaving sub sector as an icon in several regions in Bali Province like Klungkung. This study was aimed at finding out the evaluation of women empowerment management models in order to strengthen the local economy in which local governments were involved in encouraging, stimulating, maintaining business activities to create jobs. The successful implementation of the model was expanding opportunities for small communities in employment and business opportunities; expansion for the community to increase income; the empowerment of micro and small business institutions in the production and marketing process; and institutional empowerment of partnership networks between government, private sector, and local communities.